Synaptic Inputs of Neural Afferent Pathways to Vasopressin- and Oxytocin-Secreting Neurons of Supraoptic and Paraventricular Hypothalamic Nuclei - Iovino, Michele; Angelo Giagulli, Vito; Licchelli, Brunella; Iovino, Emanuela; Guastamacchia, Edoardo; Triggiani, Vincenzo (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2016)
Background: Magnocellular neurosecretory neurons of the hypothalamic supraoptic (SON) and paraventricular (PVN) nuclei synthesize vasopressin and oxytocin in response to signals generated by osmoreceptors and baroreceptors and, respectively, by receptors of the nipples and cervix. Methods: We analyzed the literature identifying relevant articles dealing with synaptic inputs of neural afferent pathways to Vasopressin-and Oxytocin-secreting neurons of SON and PVN. Results: This article focuses on the multisynaptic pathways involved in the regulation of Vasopressin and Oxytocin secretion. Conclusion: An updated topographic description of the afferent pathways involved in the regulation of VPergic and OTergic neurons and their synaptic inputs inducing the stimulus-secretion-coupling has been depicted.
Keywords: Circumventricular organs